Analysis of Split Air Conditioner Noise using Sound Intensity Mapping - M. S. M., Sani; Izzuddin, Zaman; M. M., Rahman (Akademi Baru, 2015)
This paper describes the noise generation and noise source identification for air conditioner noise using sound intensity method. Split unit air conditioners have an indoor unit and an outdoor unit connected by communication pipes. Noise can be reduced the efficiency and performance of the air conditioner. In order to identify and analysis of noise at air conditioner system, experiment has been conducted using sound intensity mapping method. The investigation is carried out by varying the parameters which are the fan speed and temperature. A grid rig was developed to set noise location and rating by locating the microphone at rig point. The noise mapping is presented in contour form to indicate the different level of noises from different location. The highest noise sound levels occur at the front side of air conditioner which is about 74.78 dB at the fan. The second highest noise sound level is occur at the right side of the compressor is 72.11dB. Sound power level is proportional to fan speed at the lowest temperature of the air conditioner. This method can be applied on-site rather than in an anechoic chamber as long as the background noises are stationary.